Novel CuxFeMnNiSnTi high entropy alloys: Microstructure, surface chemistry, and corrosion resistance - Leandro Santos da Silva; Tiago Luiz Ferreira; Mara Cristina Lopes de Oliveira; Renato Altobelli Antunes; Ricardo Alexandre Galdino da Silva (Journal of Materials Research and Technology, 2023)
CuxFeMnNiSnTi alloys were prepared by electric arc melting. The microstructure was examined by scanning electron microscopy and the crystalline phases were assessed by X-ray diffractometry. The composition of the surface oxide film was analyzed by X-ray photoelectron spectroscopy. The corrosion resistance was studied by electrochemical impedance spectroscopy and potentiodynamic polarization. Depending on the copper content, the microstructures were comprised of (Cu,Mn,Ni)3Sn, Ti(Ni,Fe)2Sn, and (Fe,Mn)2Ti. The oxide films consisted of a complex mixture of different oxide phases. The corrosion resistance was affected by the copper content and was mainly influenced by the alloy microstructure than the composition of the oxide film.